Exploring the mechanisms underlying firms' intent to adopt circular business models - Tu Tran-Thi-Thanh; Anh Nguyen-Thi-Phuong (Contemporary Economics, 2023)
Firms play a vital role in the transition towards a circular economy (CE). However, the number of firms implementing CE initiatives, or circular business models (CBMs-economic models based on CE principles), is currently small. In light of this, this study quantitatively assesses the critical factors that influence firms' intentions to adopt CBMs, with the theories of Planned Behavior and the Resource-based View providing the theoretical background. We applied the PLS-SEM to 321 firms and found that attitude and perceived behavioral control of firm owners/managers, as well as long-term orientation and social pressure of firms, significantly influence the intention to adopt CBMs, with perceived behavioral control emerging as the most influential factor. The findings also confirm that finance and knowledge have a crucial influence on firm owners'/managers' perceptions of the conditions necessary to undertake CBMs. Overall, then, the study provides sound policy implications and scholarly evidence to fill the relevant research gap, and in so doing contributes to ensuring a better transition towards a CE.
Keywords: Q01; Q56; D02; 330; circular business model; circular economy; intention; TPB; PLS-SEM